Penerapan Model Discovery Learning dalam Pembelajaran Bahasa Arab - Yunitra, Amirah Salsabila; Mappasiara (Al Asma: Journal of Islamic Education, 2024)
This research aims to determine the application of the discovery learning model in Arabic language learning. This research is a Pre-Experimental quantitative research. This research design is a one-group pretest-posttest, which uses one group without a comparison group. The sample of this research is grade VII, with 22 students in total. The methods of data collection used are tests and documentation. The data analysis technique used is descriptive and inferential statistical analysis with the t-test. Based on the results of the descriptive analysis, the research result of the overall average score before the application of the discovery learning model is 37. Meanwhile, the research result of the overall average score after the application of the discovery learning model is 87. Furthermore, the inferential statistical analysis showed that this discovery learning model could improve Arabic language learning in grade VII at the Darul Aman Takalar Islamic Boarding School. This research implies that the discovery learning model can be used as an alternative in the Arabic language learning process.